Diffuse Pneumatosis Cystoides Intestinalis in a Pig - Eroksuz, Yesari; İncili, Canan Akdeniz; Karabulut, Burak; Aksoy, Mehmet; Eröksüz, Hatice (My University, 2021)
Morphological and immunohistochemical features of a diffuse pneumatosis cystoides intestinaliscase was described in an adult pig. Gas filled cysts were present in large and small intestinalserosa and the wall of cysts were immunopositive to podoplanin antibody indicating the cysts wereactually gas filled lymph vessels. As a result, the present case report clearly demonstrated thatcystic structures proved to be dilated lymphatic vessels.
Keywords: Biyoloji; Patoloji; Veterinerlik